2012
DOI: 10.1371/journal.pone.0043165
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Oxygenation Is Highly Sensitive to Blood Pressure Variability in Sick Preterm Infants

Abstract: ObjectivesThe significance of blood pressure variability (BPV) for cerebral oxygenation in extremely preterm infants has not been explored, though BPV may well be associated with end organ injury. We hypothesized that increased BPV in sick preterm infants, by exceeding the cerebral autoregulatory capacity, is associated with cerebral oxygenation changes which closely follow the blood pressure fluctuations. We assessed the autoregulatory capacity in the early postnatal period, by determining the correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 28 publications
4
58
0
Order By: Relevance
“…A significant statistical correlation between cerebral blood flow systolic velocity and systemic blood pressure can provide information regarding the status of autoregulatory mechanisms within the cerebral vasculature. Previous studies assessing cerebral autoregulation have suggested that sick preterm infants frequently have impaired autoregulation primarily during periods of hypotension (4,(14)(15)(16). Whereas, normotensive preterm infants maintain autoregulation (17).…”
Section: Discussionmentioning
confidence: 99%
“…A significant statistical correlation between cerebral blood flow systolic velocity and systemic blood pressure can provide information regarding the status of autoregulatory mechanisms within the cerebral vasculature. Previous studies assessing cerebral autoregulation have suggested that sick preterm infants frequently have impaired autoregulation primarily during periods of hypotension (4,(14)(15)(16). Whereas, normotensive preterm infants maintain autoregulation (17).…”
Section: Discussionmentioning
confidence: 99%
“…19 Phase shift has not been reported for studies of CA in neonates based on spontaneous fluctuations in MAP. 8,10,[20][21][22][23] This might be due to the fact that the interpretation of phase over a frequency range is difficult. What does the average phase shift in a frequency band actually mean?…”
Section: Can We Handle the Phase Shift Between The Two Signals?mentioning
confidence: 99%
“…Increased systemic cytokines in premature infants with chorioamnionitis are associated with hemodynamic disturbances leading to cerebral hypoxia/ischemia, whereas co-morbid chorioamnionitis and placental perfusion defect put preterm infants at higher risk of abnormal neurologic outcomes than either insult alone [7,8,9]. Similarly, animal studies have demonstrated systemic inflammation induced by lipopolysaccharide sensitizes hypoxic/ischemic injury in the immature brain [10].…”
Section: Introductionmentioning
confidence: 99%